2019
DOI: 10.3389/fnins.2019.00710
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Cognitive Function: A Systematic Review

Abstract: Background: Autonomic dysfunctions may precede the development of cognitive impairment, but the connection between these dimensions is unclear. This systematic review aims to analyze the relationship between heart rate variability (HRV) and cognitive functions. Methods: The review process was conducted according to the PRISMA-Statement. Restrictions were made, selecting the studies in English and published in peer-review journals, including at least one cognitive measure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
349
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 386 publications
(381 citation statements)
references
References 73 publications
(199 reference statements)
23
349
2
7
Order By: Relevance
“…In fact, the autonomic profile of hypertensive and normotensive people is different [106]. Autonomic dysfunctions, in particular, a sympathetic predominance, seem to be related to cognitive impairment and to worse performance in different cognitive domains (for a review see [113]).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the autonomic profile of hypertensive and normotensive people is different [106]. Autonomic dysfunctions, in particular, a sympathetic predominance, seem to be related to cognitive impairment and to worse performance in different cognitive domains (for a review see [113]).…”
Section: Discussionmentioning
confidence: 99%
“…A future study could consider anxiety and arousal measures to support the findings from this study and the idea that hypertensive individuals could express their emotions through the physiological components. For example, it could be useful to consider the Heart Rate Variability measure that could be given more information about physiological activation (e.g., Forte et al, 2019).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Hillebrand et al (2013) reported that healthy subjects with diminished resting HRV have a 32-45% increased risk to suffer from a first cardiovascular event [11]. Furthermore, HRV is thought to be associated with cognitive performance and emotional well-being (see reviews [12,13]). Whether these correlational associations describe HRV as a consequence of central regulatory processes or as a prerequisite for effective regulation is still unclear [14].…”
Section: Introductionmentioning
confidence: 99%